The effectiveness, efficiency, and acceptability of EMDR vs. EMDR 2.0 vs. the Flash technique in the treatment of patients with PTSD: study protocol for the ENHANCE randomized controlled trial - Alting van Geusau, Valentijn V. P.; de Jongh, Ad; Nuijs, Mae D.; Brouwers, Thomas C.; Moerbeek, Mirjam; Matthijssen, Suzy J. M. A. (Frontiers in Psychiatry, 2023)
Background Several widely studied therapies have proven to be effective in the treatment of post-traumatic stress disorder (PTSD). However, there is still room for improvement because not all patients benefit from trauma-focused treatments. Improvements in the treatment of PTSD can be achieved by investigating ways to enhance existing therapies, such as eye movement desensitization and reprocessing (EMDR) therapy, as well as exploring novel treatments. The purpose of the current study is to determine the differential effectiveness, efficiency, and acceptability of EMDR therapy, an adaptation of EMDR therapy, referred to as EMDR 2.0, and a novel intervention for PTSD, the so-called Flash technique. The second aim is to identify the moderators of effectiveness for these interventions. This study will be conducted among individuals diagnosed with PTSD using a randomized controlled trial design. Methods A total of 130 patients diagnosed with (complex) PTSD will be randomly allocated to either six sessions of EMDR therapy, EMDR 2.0, or the Flash technique. The primary outcomes used to determine treatment effectiveness include the presence of a PTSD diagnosis and the severity of PTSD symptoms. The secondary outcomes of effectiveness include symptoms of depression, symptoms of dissociation, general psychiatric symptoms, and experiential avoidance. All patients will be assessed at baseline, at 4-week post-treatment, and at 12-week follow-up. Questionnaires indexing symptoms of PTSD, depression, general psychopathology, and experiential avoidance will also be assessed weekly during treatment and bi-weekly after treatment, until the 12-week follow-up. Efficiency will be assessed by investigating the time it takes both to lose the diagnostic status of PTSD, and to achieve reliable change in PTSD symptoms. Treatment acceptability will be assessed after the first treatment session and after treatment termination. Discussion This study is the first to investigate EMDR 2.0 therapy and the Flash technique in a sample of participants officially diagnosed with PTSD using a randomized controlled trial design. This study is expected to improve the available treatment options for PTSD and provide therapists with alternative ways to choose a therapy beyond its effectiveness by considering moderators, efficiency, and acceptability. Trial registration The trial was retrospectively registered in the ISRCTN registry at 10th November 2022 under registration number ISRCTN13100019.